Role of Anger Management in Cultivating Resilience among young people: Counselling Implications - Tibi, P.I.; Omumu, F.C.; Chenube, O.O. (Direct Research Journal of Education and Vocational Studies, 2023)
This paper examines the crucial connection between the ability to control anger and the capacity to bounce back from adversity, specifically in the context of young people’s growth and progress. The research explores the impact of good anger management on emotional well-being, adaptive problem-solving, and enhanced social competence in young individuals, recognising the crucial role of resilience in overcoming adversities during adolescence and early adulthood. The study investigates the effects of different anger management techniques, including deep breathing, mindfulness, cognitive restructuring, and confident speaking, on emotional well-being and overall resilience. The discourse highlights the need for early intervention and the involvement of anger management programmes, such as Cognitive Behavioural Therapy (CBT), mindfulness techniques, and peer support programmes. This discussion provides suggestions for educators, parents, and professionals. It promotes the inclusion of anger management in comprehensive resilience programmes, emphasising cooperation, cultural awareness, and ongoing assessment to guarantee the overall growth and resilience of young individuals.